Mountain ecosystem response to global change - Löffler, Jörg; Anschlag, Kertsin; Baker, Barry; Finch, Oliver-D.; Diekkrüger, Bernd; Wundram, Dirk; Schröder, Boris; Pape, Roland; Lundberg, Anders (ERDKUNDE, 2011)
Mountain ecosystems are commonly regarded as being highly sensitive to global change. Due to the system complexity and multifaceted interacting drivers, however, understanding current responses and predicting future changes in these ecosystems is extremely difficult. We aim to discuss potential effects of global change on mountain ecosystems and give examples of the underlying response mechanisms as they are understood at present. Based on the development of scientific global change research in mountains and its recent structures, we identify future research needs, highlighting the major lack and the importance of integrated studies that implement multi-factor, multi-method, multi-scale, and interdisciplinary research.